Trends in mobilisation and unionisation in South Africa and Germany: a comparative analysis - Whiteley, Julianne Beverley (Rhodes University, Faculty of Humanities, Department of Sociology, 2001)
The purpose of this study is to investigate long-term trends in the union membership of South Africa and Germany, and to highlight trends in unionisation in both of these countries over a period of time. The long-term aspect of this study differentiates it from more detailed specific studies concerned with the individual fortunes of confederations or unions. The changing fortunes of trade unions have been associated with changes in work organisation, the influence of institutional pressures, or long term changes in the economic cycle. All these factors may, of course, shape and be shaped by each other. From a comparative perspective this dissertation determines whether the fortunes of unions are ultimately a product of the long waves of an economic cycle, or if other factors, such as variations in union/state relations, changes in the forms of work organisation and shifts in the employment market, impact upon union membership and mobilisation. It is hoped that the comparison of a transitional and an advanced economy may shed new light on the causes of union growth and decline, and the impact of specific social, legal and cultural variables thereon. The theoretical frame of reference for this study emerged from literature pertaining to union growth and decline. This literature discusses the historical, economic and sectoral challenges that confront the identity of unions and their ability to mobilise membership within contemporary labour markets. The entire study relies heavily on primary data collected from a wide range of sources in both countries. This method facilitates the comparison and cross-checking of information, which ensures a full and balanced study. A synthesis of the facts obtained led to certain suggestions relating to the areas in which both South African and German labour organisations could adapt their agenda and interests to the changing nature of the employment market in order to avert membership decline. The methodology of this research draws from Skopol's work which argues that social studies ought to be grounded in historical experience in order to make sense out of specific social events that occur today. The research design utilises an initial comparative historical-political analysis of the emergence of unionism in South Africa and Germany, so as to establish those factors which have, in the past, affected union growth and decline in both countries. Thereafter, the impact of contemporary economic and sectoral trends that reoccur in the South African and German labour markets are examined and compared, in order to establish their influence on the growth or decline of union membership in both countries in the future. This study consists of four sections. The first section comprises a historical dimension that uses Valenzuela's work relating to the political nature of labour movements to establish those factors which, in the past, have affected union growth and decline. This is done to determine whether the type of insertion of labour movements into historical national political processes, and the links formed between trade unions and political parties influences membership growth or decline. The following three sections deal with the present challenges that may affect the unions in the future. Section Two deals with factors of economic recession (namely, poverty and unemployment) which confront trade unions in the 1990s. Hyman's Theory of Disaggregation is applied to determine if recessive socio-economic factors can account for the strength of decline of unions, as opposed to union mobilisation being purely linked to transitions between long waves of the economy as Kelly suggests. The relevance of these theories to the rise and decline of unionism in South Africa and Germany is compared and contrasted. The third section determines whether changes to more flexible forms of work organisation and shifts in the employment market can account for the contrasting strength of the South African labour movement and the decline of the German labour movement today. The way in which these issues impact negatively upon union strength in South Africa and Germany in the 1990s is compared and contrasted, again using Hyman's Theory of Disaggregation. The final section establishes whether or not the roles adopted by the South African and German labour movements during their confrontation with labour repressive regimes impacts upon their ability to attract union membership today, despite the constraints imposed upon unions by prevailing economic and structural uncertainties. Therefore the historicity of the South African and German labour movements, (based upon the findings of the first part of this study), is referred back to. At the same time, the reactions of the South African and German labour movements to prevailing economic and structural realities, (as examined in the second part of this research) are re-examined. Three conclusions are reached. Firstly, regardless of their strengths or weaknesses, all labour organisations are capable of adjusting to the adverse changes taking place in contemporary employment markets if they prove willing to advance and defend the interests of all who work, including those in the informal sector. If unions continue to neglect the informal labour market, they run the risk of being transposed by social movements that are antagonistic to trade unions or new expressions of the workforce's latent collectivism. Secondly, in successfully playing a social movement role that led to the downfall of Apartheid in 1994, the South African labour movement has evolved as an energetic body with a dimension of recumbent militancy that attempts to adapt its identity to the changing nature of the employment market. This enables the South African labour movement to continue to attract membership despite the prevailing economic uncertainties. In contrast, forced co-operation and consensus within the German industrial relations arena since World War Two has resulted in a less dynamic union movement that lacks initiative in adapting to the changing nature of the employment market. The result is a decline in unionism. Finally, the fortunes of unions are not, as Kelly suggests, purely a product of economic cycles. Political climates can also influence mobilisation, as has occurred in both South Africa and Germany. This implies that mobilisation is not only activated by the economic dissatisfaction of a union movement.
Keywords: Industrial mobilization -- South Africa; Labor unions -- South Africa; Industrial mobilization -- Germany; Labor unions -- Germany; South Africa -- Economic conditions; Germany -- Economic conditions